Fatigue strength prediction of large-size component through size effect measurement and determination. (March 2023) - Bai, Xin; Zhang, Peng; Liu, Shuo; Liu, Rui; Zhao, Bingfeng; Zhang, Zhefeng
Graphical abstract: Due to lacking enough information of fatigue tests, the possible models established directly from the stress which is determined in the framework of macroscopic mechanics fail to describe the fatigue size effects on engineering components in large range. However, a new model named as the critical external load (LET) model and focused on the statistical size effects on fatigue property is first established from the critical external load (the minimum load resulting in fatigue, i.e. fatigue force or fatigue moment) and effective thickness. The LET model is validated by the testing results of the components with different shape or different loading types or different materials. Based on this model, a new method for fatigue strength prediction of components is proposed. Significantly, the LET model can be extrapolated very far, e.g. from 9.1 mm to 182 mm for the axle. Besides, the LET model is more accurate than the possible models. Therefore, the LET model can be used to describe the fatigue statistical size effects in a larger size range and the proposed method can be used for the fatigue strength prediction of the components with low cost up-and-down tests. Highlights: A new fatigue size effect model is established from the critical external loads. The new model works over a wide size range for engineering components. The fatigue strength of component is predicted with low cost and high efficiency. Abstract: Large-size components play a significant role in resisting cyclic stress failure. To reduce the cost and to improve the testing efficiency, a new model named as the critical external load (LET) model and focused on the statistical size effects on fatigue property is first established from the critical external load (the minimum load resulting in fatigue, i.e. fatigue force or fatigue moment) and effective thickness. The LET model is validated by the testing results of the components with different shape or different loading types or different materials. Accordingly, a new method for fatigue strength prediction of components is proposed in this study, including the design of specimens and the measurement and determination of fatigue statistical size effects through the up-and-down fatigue tests. And then the new method is used to predict the fatigue strength of a Chinese high-speed railway solid axle. In comparison with the testing results of the full-scale axle and the predicted values from other fatigue size effect models, the LET model can describe the fatigue size effects in a larger size range and the method as presented here can be used for the fatigue strength prediction of the large-size components with relatively low cost and high efficiency (e.g. reducing the cost by more than 96.7% and increasing the efficiency by about 50% for the full-scale axles in up-and-down tests).